2023
DOI: 10.1038/s41598-023-29035-8
|View full text |Cite
|
Sign up to set email alerts
|

Wheat husk-based sorbent as an economical solution for removal of oil spills from sea water

Abstract: Oil spills are a significant threat to the marine ecosystem that requires immediate removal from the oceanic environment. Many technologies have been employed to clean up oil spills. Of these, adsorption has scored a prominent success due to the high efficiency, economic viability, environmental friendship, and ease of application. The utilization of agricultural waste to produce biosorbents have been considered as an ecofriendly and efficient approach for removing oil. Thus, a new low-cost oil adsorbent was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…The calculated R L value was found to be 0.749 and 0.706 for the used fungal biomass and the extracellular melanin, respectively. The biosorption process’s nature is distinguished by the R L value, e.g., unfavorable R L > 1); linear (R L = 1); favorable (0 < R L < 1); irreversible (R L = 0) [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated R L value was found to be 0.749 and 0.706 for the used fungal biomass and the extracellular melanin, respectively. The biosorption process’s nature is distinguished by the R L value, e.g., unfavorable R L > 1); linear (R L = 1); favorable (0 < R L < 1); irreversible (R L = 0) [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The calculated R L value was found to be 0.749 and 0.706 for the used fungal biomass and the extracellular melanin, respectively. The biosorption process's nature is distinguished by the R L value, e.g., unfavorable R L > 1); linear (R L = 1); favorable (0 < R L < 1); irreversible (R L = 0) [67,68]. The obtained R L value indicated that the Cr(VI) biosorption onto the used fungal biomass or the extracellular melanin was a favorable process.…”
Section: Biosorption Isothermsmentioning
confidence: 99%
“…23 Similarly, various sorbent materials were synthesized and used for oil spill cleanup. [24][25][26][27][28][29] Crosslinking and various polymer analogous reactions have been used to tailor these bio-wastes for such oil spill applications. 30,31 Using biowaste can also serve to tackle another major problem: its disposal and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%